(untitled) (Research, Society and Development, 2022)
Objective: to analyze the interference of the COVID-19 pandemic on the donation of breast milk in a public maternity hospital in the north of Minas Gerais. Methodology: this is a documentary and descriptive study, carried out in May and June 2022, considering the data from 2019 to 2021 from the Billing Book of the human milk collection point and in four notebooks of occurrences of the lactary. The research was approved by opinion 4,272,156. Results: in 2019, 269 donors were registered, a total of 390.97 milliliters of breast milk were collected, and delivered to 186 newborns admitted to the hospital. From 2019 to 2020, the number of donors increased and 17 more newborns were benefited. From 2020 to 2021 there were 29 fewer donors, but the amount of milk donated was greater. Discussion: even though the year 2021 ended with a reduced number of donors, the milking was more successful than in the years 2019 and 2020. A possible hypothesis for the result of this research to have been beneficial is that the hospital in question works with continuing education for hospitalized puerperal women as an incentive to donate human milk and collect milk through home visits. Final Considerations: this research concluded that the COVID-19 pandemic did not interfere with the donation of HM to newborns admitted to one of the hospitals in the north of Minas. This study shows the importance of continuing education as an incentive for breastfeeding and human milk donation for hospitalized newborns.